Behind the wall: Macrolithic artifacts as testing tools for activities and social structure on a Middle Chalcolithic site in Central Anatolia - Jaroslav Řídký; Kristina Doležalová; Daniel Pilař; Pınar Çaylı; Işıl Demirtaş; Sevil Gülçur (PLoS ONE, 2025)
The main focus of this work is an assemblage of nearly two thousand macrolithic artifacts, weighing more than half a metric ton, retrieved from an excavated area measuring 3,600 m2 of the Middle Chalcolithic site of Güvercinkayası, which dates from the end of the 6th and first half of the 5th millennium cal BCE. The site is ideal for testing different analytical approaches due to the extent of the excavated area, the good preservation of structures and finds, the site layout and the fact that the site is divided into two parts by a fortification wall. Macrolithic artifacts were divided into ten classes according to the method of manufacture, raw materials, shapes and dimensions, and their functional use. Several examples were chosen for use-wear analysis of the active surfaces. The Middle Chalcolithic period in Central Anatolia represents the end of previous Neolithic traditions in architecture and ways of life. Therefore, the main objective of our work is to present the assemblage from this period, and further to test the information potential of these artifacts for studying the activities and social structure of settlements. The shape spectrum of the assemblage largely corresponds to the Neolithic period. It differs mainly in the proportion of some shapes and functional types present. In addition, certain artifacts appear to indicate the existence of some form of counting system or board game. Based on the results of the study of macrolithic artifacts and their statistical and spatial analysis, it is clear that the composition of artifacts and access to raw materials was similar in different parts of the settlement. The inhabitants of the Middle Chalcolithic site created a settlement with a regular layout, which at a certain time was divided into two parts. However, the results of our analyses do not demonstrate any significant patterns that would testify to vertical social stratification of the society living within this settlement.